Challenges For Capital Market Investors Post Effectiveness UU No.4 Of 2023 Concernng Development and Strengthening The Financial Sector In Indonesia - Wulan Wuryandari, Rr. Utji Sri; Surono, Agus; Akkapin, Supaphorn (CV. Era Digital Nusantara, 2024)
The aims of this study are: firstly, to examine the legal protection of capital market investors after the enactment of Law No. 4 of 2023 concerning Development and Strengthening of the Financial Sector; and secondly, to examine the implementation of Article 49 paragraph (5) of Law No. 4 of 2023 concerning Development and Strengthening of the Financial Sector which regulates the authority of the Financial Services Authority (OJK) as the sole investigator in the financial services sector, especially in the capital market field. This study uses normative research methods and a qualitative analysis approach. This study concludes that legal protection for capital market investors cannot fully follow what is regulated and mandated by law in the financial sector. This is hampered by the rejection of judicial review regarding laws in the financial sector. The next conclusion is that Article 49 paragraphs (1) and (5) which regulate the authority of the OJK as the sole investigator in the financial services sector cannot yet be implemented due to Constitutional Court Decision No. 59/PUU-XXI/2023. The Constitutional Court's decision granted the lawsuit so that the investigative authority for criminal acts in the financial services sector continues to involve the Police in addition to the OJK. Because Article 49 of Law No. 4 of 2023 cannot be applied to OJK's authority, so the implementation of its authority continues to follow Law No. 21 of 2011 concerning the Financial Services Authority. Furthermore, this study is aimed at realizing a more comprehensive arrangement in the financial sector, especially in the capital markets sector